EFFICACY OF CURCUMIN AS AN ADJUNCT TO SCALING AND ROOT PLANING IN PERIODONTITIS PATIENTS – A CLINICAL AND MICROBIOLOGICAL STUDY - Karthickeyan, P.; Bhaskar, J.; Mahalakshmi, K.; Prasanth, B. Krishna; Gita, Bhagavad; Valiyathan, Mohan; Balaji, Anitha (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: The goal of periodontal therapy is to eliminate bacterial plaque and the factors favoring its formation. Conventional therapy includes scaling, root planing and curettage along with appropriate maintenance of oral hygiene. However, complete elimination of sub gingival micro flora is difficult from areas inaccessible to periodontal instrumentation, which demands the use of antimicrobials as adjuncts in periodontal therapy. Periodontal pocket provides an ideal environment for the growth of anaerobic pathogenic bacteria. In the course of initiation and progression of the inflammatory process, the sub gingival bacteria increase in numbers and invade the pocket epithelial cells and subsequently, the underlying tissues. Aim: To evaluate the efficacy of the adjunctive use of curcumin with scaling and root planing as compared with scaling and root planing alone in the treatment of the periodontitis. Materials and Methods: Twenty patients with two contralateral sites were identified for the study having probing pocket depths (PPDs) of >5mm. Full mouth scaling and root planing (SRP) was done followed by subgingival application of curcumin gel only on one side. Assessment of Plaque index (PI), Gingival index (GI), Probing Pocket Depth, Clinical attachment levels (CALs) were done at both baseline and at 4th week. Subgingival plaque samples was collected from the root surface and standard microbiologic assessment was done both from the control and the test sites before scaling and root planing. Result: There was a reduction in PI, GI, PPD, CAL and microbiologic parameters in test sites followed by SRP and curcumin gel application, when compared with SRP alone in control group. Conclusion: The subgingival application of curcumin gel in adjunct with scaling and root planing has shown good improvement in periodontal parameters and has a beneficial effect in periodontitis patients. Keywords: Curcumin, Periodontitis, Scaling and root planing.